Apolipoprotein A-IV concentrations and clinical outcomes in a large chronic kidney disease cohort: Results from the GCKD study - Schwaiger, Johannes P.; Kollerits, Barbara; Steinbrenner, Inga; Weissensteiner, Hansi; Schoenherr, Sebastian; Forer, Lukas; Kotsis, Fruzsina; Lamina, Claudia; Schneider, Markus; Schultheiss, Ulla T.; Wanner, Christoph; Koettgen, Anna; et al. (Journal of Internal Medicine, 2022)
Background Chronic kidney disease (CKD) represents a chronic proinflammatory state and is associated with very high cardiovascular risk. Apolipoprotein A-IV (apoA-IV) has antiatherogenic, antioxidative, anti-inflammatory and antithrombotic properties and levels increase significantly during the course of CKD. Objectives We aimed to investigate the association between apoA-IV and all-cause mortality and cardiovascular outcomes in the German Chronic Kidney Disease study. Methods This was a prospective cohort study including 5141 Caucasian patients with available apoA-IV measurements and CKD. The majority of the patients had an estimated glomerular filtration rate (eGFR) of 30-60 ml/min/1.73m(2) or an eGFR >60 ml/min/1.73m(2) in the presence of overt proteinuria. Median follow-up was 6.5 years. The association of apoA-IV with comorbidities at baseline and endpoints during follow-up was modelled adjusting for major confounders. Results Mean apoA-IV concentrations of the entire cohort were 28.9 +/- 9.8 mg/dl. Patients in the highest apoA-IV quartile had the lowest high-sensitivity C-reactive protein values despite the highest prevalence of diabetes, albuminuria and the lowest eGFR. Each 10 mg/dl higher apoA-IV translated into lower odds of prevalent cardiovascular disease (1289 cases, odds ratio = 0.80, 95% confidence interval [CI] 0.72-0.86, p = 0.0000003). During follow-up, each 10 mg/dl higher apoA-IV was significantly associated with a lower risk for all-cause mortality (600 cases, hazard ratio [HR] = 0.81, 95% CI 0.73-0.89, p = 0.00004), incident major adverse cardiovascular events (506 cases, HR = 0.88, 95% CI 0.79-0.99, p = 0.03) and death or hospitalizations due to heart failure (346 cases, HR = 0.84, 95% CI 0.73-0.96, p = 0.01). Conclusions These data support a link between elevated apoA-IV concentrations and reduced inflammation in moderate CKD. ApoA-IV appears to be an independent risk marker for reduced all-cause mortality, cardiovascular events and heart failure in a large cohort of patients with CKD.
CRIS-Team WoS Importer:2022-01-14

APOLIPOPROTEIN A-IV CONCENTRATIONS AND CLINICAL OUTCOMES IN CHRONIC KIDNEY DISEASE PATIENTS: RESULTS FROM THE GERMAN CHRONIC KIDNEY DISEASE (GCKD) STUDY - Schwaiger, J. P.; Kollerits, B.; Steinbrenner, I.; Weissensteiner, H.; Schoenherr, S.; Forer, L.; Kotsis, F.; Schneider, Markus; Schultheiss, U. T.; Wanner, C.; Koettgen, A.; Eckardt, Kai-Uwe; et al. (ATHEROSCLEROSIS, 2021)
CRIS-Team WoS Importer:2021-09-24

A randomized controlled trial of the effect of spironolactone on left ventricular mass in hemodialysis patients - Hammer, Fabian; Malzahn, Uwe; Donhauser, Julian; Betz, Christoph; Schneider, Markus; Grupp, Clemens; Pollak, Nils; Störk, Stefan; Wanner, Christoph; Krane, Vera; Berweck, Susanne; Biggar, Patrick; et al. (Kidney International, 2019)
Mineralocorticoid receptor antagonists have beneficial effects on left ventricular remodeling, cardiac fibrosis, and arrhythmia in heart failure, but efficacy and safety in dialysis patients is less clear. We evaluated the effect of spironolactone on left ventricular mass (LVM), an independent predictor of all-cause and cardiovascular mortality, in hemodialysis patients. In this placebo-controlled, parallel-group trial, 97 hemodialysis patients (23% female; mean age 60.3 years) were randomized to spironolactone 50 mg once daily (n=50) or placebo (n=47). The primary efficacy endpoint was change in LVM index (LVMi) from baseline to 40 weeks as determined by cardiac magnetic resonance imaging. Safety endpoints were development of hyperkalemia and change in residual renal function. There was no significant change in LVMi in participants randomized to spironolactone compared to placebo (-2.86±11.87 vs. 0.41±10.84 g/m2). There was also no difference in the secondary outcomes of mean 24-hour systolic or diastolic ambulatory blood pressure, left ventricular ejection fraction, 6-minute walk test distance, or New York Heart Association functional class. Moderate hyperkalemia (pre-dialysis potassium levels of 6.0-6.5 mmol/L) was more frequent with spironolactone treatment (155 vs. 80 events), but severe hyperkalemia (≥6.5 mmol/L) was not (14 vs. 24 events). Changes in residual urine volume and measured glomerular filtration rate did not differ between groups. There were no deaths in the spironolactone group and 4 deaths in the placebo group. Thus, treatment with 50 mg spironolactone did not change left ventricular mass index, cardiac function, or blood pressure in hemodialysis patients. Spironolactone increased the frequency of moderate hyperkalemia, but did not increase severe hyperkalemia.
EVALuna2:36276

Association Between Dietary Patterns and Kidney Function in Patients With Chronic Kidney Disease: A Cross-Sectional Analysis of the German Chronic Kidney Disease Study - Heindel, Judith; Baid-Agrawal, Seema; Rebholz, Casey M.; Nadal, Jennifer; Schmid, Matthias; Schaeffner, Elke; Schneider, Markus; Meiselbach, Heike; Kaesler, Nadine; Bergmann, Manuela; Ernst, Sabine; Krane, Vera; et al. (Journal of Renal Nutrition, 2019)
Objective: In the general population, “healthy” dietary patterns are associated with improved health outcomes, but data on associations between observance of specific dietary patterns and kidney function in patients with chronic kidney disease (CKD) are sparse. Methods: Dietary intake was evaluated using food frequency questionnaires in patients with moderately severe CKD under nephrology care enrolled into the observational multicenter German CKD study. The Dietary Approaches to Stop Hypertension (DASH) diet score, Mediterranean diet score, and German Food Pyramid Index (GFPI) were calculated and their association with estimated glomerular filtration rate (eGFR) and albuminuria was assessed by multivariable linear regression analysis, adjusted for gender, age, body mass index, energy intake, smoking status, alcohol intake, education, high-density lipoprotein-cholesterol (HDL- cholesterol), low-density lipoprotein-cholesterol (LDL-cholesterol), hypertension, and diabetes mellitus. Results: A total of 2,813 patients (41% women; age 60.1 ± 11.6 years) were included in the analysis. High DASH diet score and GFPI were associated with lower systolic blood pressure and lower intake of antihypertensive medication, higher HDL, and lower uric acid levels. Mediterranean-style diet was associated with lower prevalence of diabetes mellitus. Higher DASH and Mediterranean diet scores were associated with higher eGFR (β-coefficient = 1.226, P <.001; β-coefficient = 0.932, P =.007, respectively). In contrast, GFPI was not associated with eGFR. For the individual components of the dietary patterns, higher intake of nuts and legumes, cereals, fish, and polyunsaturated fats was associated with higher eGFR and higher intake of dairy, composed of low- and whole-fat dairy, was associated with lower eGFR. No association was found between dietary patterns and albuminuria. Conclusion: Higher observance of the DASH or Mediterranean diet, but not German food pyramid recommendations, was associated with higher eGFR among patients with CKD. Improving dietary habits may offer an opportunity to better control comorbidities and kidney function decline in patients with CKD.
CRIS-Team Scopus Importer:2019-12-27

Association of mineral and bone biomarkers with adverse cardiovascular outcomes and mortality in the German Chronic Kidney Disease (GCKD) cohort - Reimer, Katharina Charlotte; Nadal, Jennifer; Meiselbach, Heike; Schmid, Matthias; Schultheiss, Ulla T.; Kotsis, Fruzsina; Stockmann, Helena; Friedrich, Nele; Nauck, Matthias; Krane, Vera; Eckardt, Kai-Uwe; Schneider, Markus; et al. (Bone Research, 2023)
Mineral and bone disorder (MBD) in chronic kidney disease (CKD) is tightly linked to cardiovascular disease (CVD). In this study, we aimed to compare the prognostic value of nine MBD biomarkers to determine those associated best with adverse cardiovascular (CV) outcomes and mortality. In 5 217 participants of the German CKD (GCKD) study enrolled with an estimated glomerular filtration rate (eGFR) between 30–60 mL·min−1 per 1.73 m2 or overt proteinuria, serum osteoprotegerin (OPG), C-terminal fibroblast growth factor-23 (FGF23), intact parathyroid hormone (iPTH), bone alkaline phosphatase (BAP), cross-linked C-telopeptide of type 1 collagen (CTX1), procollagen 1 intact N-terminal propeptide (P1NP), phosphate, calcium, and 25-OH vitamin D were measured at baseline. Participants with missing values among these parameters (n = 971) were excluded, leaving a total of 4 246 participants for analysis. During a median follow-up of 6.5 years, 387 non-CV deaths, 173 CV deaths, 645 nonfatal major adverse CV events (MACEs) and 368 hospitalizations for congestive heart failure (CHF) were observed. OPG and FGF23 were associated with all outcomes, with the highest hazard ratios (HRs) for OPG. In the final Cox regression model, adjusted for CV risk factors, including kidney function and all other investigated biomarkers, each standard deviation increase in OPG was associated with non-CV death (HR 1.76, 95% CI: 1.35–2.30), CV death (HR 2.18, 95% CI: 1.50–3.16), MACE (HR 1.38, 95% CI: 1.12–1.71) and hospitalization for CHF (HR 2.05, 95% CI: 1.56–2.69). Out of the nine biomarkers examined, stratification based on serum OPG best identified the CKD patients who were at the highest risk for any adverse CV outcome and mortality.
CRIS-Team Scopus Importer:2023-11-10

Association of osteopontin with kidney function and kidney failure in chronic kidney disease patients: the GCKD study - Steinbrenner, Inga; Sekula, Peggy; Kotsis, Fruzsina; Von Cube, Maja; Cheng, Yurong; Nadal, Jennifer; Schmid, Matthias; Schneider, Markus; Krane, Vera; Nauck, Matthias; Eckardt, Kai-Uwe; Schultheiss, Ulla T. (Nephrology Dialysis Transplantation, 2022)
Background Osteopontin (OPN), synthesized in the thick ascending limb of Henle's loop and in the distal tubule, is involved in the pathogenesis of kidney fibrosis, a hallmark of kidney failure (KF). In a cohort of chronic kidney disease (CKD) patients, we evaluated OPN's association with kidney markers and KF. Methods OPN was measured from baseline serum samples of German Chronic Kidney Disease study participants. Cross-sectional regression models for estimated glomerular filtration rate (eGFR) and urinary albumin-to-creatinine ratio (UACR) as well as Cox regression models for all-cause mortality and KF were evaluated to estimate the OPN effect. Additionally, the predictive ability of OPN and time-dependent population-attributable fraction were evaluated. Results Over a median follow-up of 6.5 years, 471 KF events and 629 deaths occurred among 4950 CKD patients. One-unit higher log(OPN) was associated with 5.5 mL/min/1.73 m(2) lower eGFR [95% confidence interval (95% CI) -6.4 to -4.6] and 1% change in OPN with 0.7% higher UACR (estimated effect 0.7, 95% CI 0.6-0.8). Moreover, higher OPN levels were associated with a higher risk of KF [hazard ratio (HR) 1.4, 95% CI 1.2-1.7] and all-cause mortality (HR 1.5, 95% CI 1.3-1.8). After 6 years, 31% of the KF events could be attributed to higher OPN levels (95% CI 3%-56%). Conclusions In this study, higher OPN levels were associated with kidney function markers worsening and a higher risk for adverse outcomes. A larger proportion of KF could be attributed to higher OPN levels, warranting further research on OPN with regards to its role in CKD progression and possible treatment options.
CRIS-Team WoS Importer:2022-07-22

Association of Serum Afamin Concentrations With Kidney Failure in Patients With CKD: Findings From the German CKD Cohort Study - Kollerits, Barbara; Kotsis, Fruzsina; Schneider, Markus; Schultheiss, Ulla T.; Weissensteiner, Hansi; Schönherr, Sebastian; Forer, Lukas; Meiselbach, Heike; Wanner, Christoph; Eckardt, Kai-Uwe; Dieplinger, Hans; Kronenberg, Florian (American Journal of Kidney Diseases, 2025)
Rationale & Objective: Afamin is a vitamin E-binding glycoprotein primarily expressed in the liver and kidney. This study investigated whether serum afamin concentrations are associated with kidney function and incident kidney failure. Study Design: Prospective cohort study with 6.5 years follow-up. Setting & Participants: 5,041 White patients enrolled in the German Chronic Kidney Disease (GCKD) study with measured afamin concentrations and either an estimated glomerular filtration rate (eGFR) of 30-60 mL/min/1.73 m2 or an eGFR > 60 mL/min/1.73 m2 with a urinary albumin-creatinine ratio (UACR) of ≥300 mg/g at study entry. Exposure: Serum afamin concentrations (mg/L). Outcome: Incident kidney failure (initiation of kidney replacement therapy or kidney-related death). Analytical Approach: Generalized linear regression and quantile regression models fit to investigate the association of afamin concentrations with eGFR and UACR. Adjusted Cox regression analysis to examine the association of afamin concentrations with incident kidney failure. Results: The mean ± SD afamin concentration at study entry was 73.2 ± 17.6 mg/L. Higher afamin concentrations were associated with better kidney function with a 2.60 mL/min/1.73 m2 higher eGFR (95% CI, 2.30-2.89) and a 5.97 mg/g lower UACR (95% CI, 3.04-8.90) for each 10 mg/L higher level of afamin concentration in adjusted analysis. During the follow-up period, each 10 mg/L higher level of afamin concentration was associated with a 14% lower risk of kidney failure (HR, 0.86 [95%CI, 0.81-0.92], P < 0.001). Limitations: Residual confounding, and potential limited generalizability to non-White populations and people with mild stages of chronic kidney disease (CKD) or no CKD. Conclusions: Higher serum afamin concentrations appear to be associated with a higher eGFR, less albuminuria, and a lower risk for future kidney failure in patients with CKD.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Afamin; chronic kidney disease; high risk population; kidney failure; prospective study

ASSOCIATION OF SERUM UROMODULIN WITH DEATH, CARDIOVASCULAR AND RENAL EVENTS: RESULTS FROM THE GERMAN CHRONIC KIDNEY DISEASE (GCKD) STUDY - Steubl, Dominik; Schneider, Markus; Meiselbach, Heike; Nadal, Jennifer; Saritas, Turgay; Krane, Vera; Sommerer, Claudia; Baid-Agrawal, Seema; Koettgen, Anna; Eckardt, Kai-Uwe; Scherberich, Juergen (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-11-26

Association of Serum Uromodulin with Death, Cardiovascular Events, and Kidney Failure in CKD - Steubl, Dominik; Schneider, Markus; Meiselbach, Heike; Nadal, Jennifer; Schmid, Matthias C.; Saritas, Turgay; Krane, Vera; Sommerer, Claudia; Baid-Agrawal, Seema; Voelkl, Jakob; Kotsis, Fruzsina; Köttgen, Anna; et al. (Clinical Journal of the American Society of Nephrology, 2020)
BACKGROUND AND OBJECTIVES: Uromodulin is exclusively produced by tubular epithelial cells and released into urine and serum. Higher serum uromodulin has been associated with lower risk for kidney failure in Chinese patients with CKD and with lower risk for mortality in the elderly and in patients undergoing coronary angiography. We hypothesized that lower serum uromodulin is associated with mortality, cardiovascular events, and kidney failure in white patients with CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We measured serum uromodulin in 5143 participants enrolled in the German CKD (GCKD) study. The associations of baseline serum uromodulin with all-cause mortality, major adverse cardiovascular events (MACE; a composite of cardiovascular mortality, nonfatal myocardial infarction or stroke, or incident peripheral vascular disease), and kidney failure (dialysis or transplantation) were evaluated using multivariable Cox proportional hazard regression analyses in a cohort study design, adjusting for demographics, eGFR, albuminuria, cardiovascular risk factors, and medication. RESULTS: The mean age of participants was 60±12 years, 60% were male. Mean serum uromodulin concentration was 98±60 ng/ml, eGFR was 49±18 ml/min per 1.73 m2, and 78% had eGFR <60 ml/min per 1.73 m2. Participants in lower serum uromodulin quartiles had lower eGFR and higher albuminuria, prevalence of diabetes, hypertension, coronary artery disease, and more frequent history of stroke at baseline. During a follow-up of 4 years, 335 participants died, 417 developed MACE, and 229 developed kidney failure. In multivariable analysis, the highest serum uromodulin quartile was associated with lower hazard for mortality (hazard ratio [HR], 0.57; 95% CI, 0.38 to 0.87), MACE (HR, 0.63; 95% CI, 0.45 to 0.90), and kidney failure (HR, 0.24; 95% CI, 0.10 to 0.55) compared with the lowest quartile. CONCLUSIONS: Higher serum uromodulin is independently associated with lower risk for mortality, cardiovascular events, and kidney failure in white patients with CKD. CLINICAL TRIAL REGISTRY NAME AND REGISTRATION NUMBER: Deutsches Register für Klinische Studien (DRKS; German national database of clinical studies), DRKS00003971.
CRIS-Team Scopus Importer:2020-05-26
Keywords: albuminuria; cardiovascular diseases; chronic; chronic kidney disease; confidence intervals; coronary angiography; coronary artery disease; diabetes mellitus; end-stage renal disease; epithelial cells; glomerular filtration rate; hypertension; myocardial infarction; peripheral vascular diseases; regression analysis; renal insufficiency; risk factors; stroke; Tamm–Horsfall protein; tubular function; uromodulin

Basal nitric oxide activity is an independent determinant of arteriolar structure in the human retinal circulation - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Schneider, Markus; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2011)
Experimental data indicate that nitric oxide might play a role in structure and remodeling of peripheral small arteries and arterioles. We hypothesized that retinal arteriolar structure is modulated by basal nitric oxide activity.The study cohort comprised 97 male untreated patients with normal and elevated blood pressure but without clinical evidence for cardiovascular disease. The changes of retinal capillary blood flow (RCF) to nitric oxide synthase inhibitor N-monomethyl-L-arginine (L-NMMA), that reflects basal nitric oxide activity of retinal vasculature, and to flicker light, that in part nitric oxide dependently provokes retinal vasodilatation, and parameters of retinal arteriolar structure, for example wall-to-lumen ratio (WLR), were assessed noninvasively and in vivo by scanning laser Doppler flowmetry.Participants were stratified according to the median WLR of retinal arterioles into two groups. In the group with WLR above the median RCF in response to infusion of L-NMMA decreased to a smaller extent (-3.82 ± 26 vs. -26.0 ± 45 arbitrary units and -0.83 ± 8.4 vs. -5.88 ± 11%, P = 0.004 and P = 0.015; respectively), whereas RCF in response to flicker light did not differ significantly compared to the counter group (22.2 ± 56 vs. 39.8 ± 51 arbitrary units and 7.42 ± 15 vs. 11.9 ± 14%, P = 0.112 and P = 0.149). In the whole study cohort WLR of retinal arterioles was related with the decrease of RCF to L-NMMA infusion [when expressed in absolute terms (r = 0.252, P = 0.013) and in percentage change (r = 0.213, P = 0.036)] and inversely related with the change of RCF to flicker light [when expressed in absolute terms (r = -0.203, P = 0.048) but not clearly when expressed in percentage change (r = -0.161, P = 0.120)]. Adjustment for major cardiovascular risk factors and changes of systemic hemodynamics in response to L-NMMA infusion revealed an independent relationship between WLR of retinal arterioles and percentage change of RCF to L-NMMA infusion (ß = 0.300, P = 0.007).Basal nitric oxide activity emerged as an independent determinant of arteriolar remodeling in the human retinal circulation in vivo.
EVALuna2:3475

Blood pressure control in chronic kidney disease: A cross-sectional analysis from the German Chronic Kidney Disease (GCKD) study - Schneider, Markus; Hilgers, Karl Friedrich; Schmid, Matthias; Hübner, Silvia; Nadal, Jennifer; Seitz, David; Busch, Martin; Haller, Hermann; Köttgen, Anna; Kronenberg, Florian; Baid-Agrawal, Seema; Schlieper, Georg; et al. (PLoS ONE, 2018)
We assessed the prevalence, awareness, treatment and control of hypertension in patients with moderate chronic kidney disease (CKD) under nephrological care in Germany. In the German Chronic Kidney Disease (GCKD) study, 5217 patients under nephrology specialist care were enrolled from 2010 to 2012 in a prospective observational cohort study. Inclusion criteria were an estimated glomerular filtration rate (eGFR) of 30-60 mL/min/1.73 m2 or overt proteinuria in the presence of an eGFR>60 mL/min/1.73 m2. Office blood pressure was measured by trained study personnel in a standardized way and hypertension awareness and medication were assessed during standardized interviews. Blood pressure was considered as controlled if systolic < 140 and diastolic < 90 mmHg. In 5183 patients in whom measurements were available, mean blood pressure was 139.5 ± 20.4 / 79.3 ± 11.8 mmHg; 4985 (96.2%) of the patients were hypertensive. Awareness and treatment rates were > 90%. However, only 2456 (49.3%) of the hypertensive patients had controlled blood pressure. About half (51.0%) of the patients with uncontrolled blood pressure met criteria for resistant hypertension. Factors associated with better odds for controlled blood pressure in multivariate analyses included younger age, female sex, higher income, low or absent proteinuria, and use of certain classes of antihypertensive medication. We conclude that blood pressure control of CKD patients remains challenging even in the setting of nephrology specialist care, despite high rates of awareness and medication use.
EVALuna2:156740

Blood Pressure Pattern and Target Organ Damage in Patients With Chronic Kidney Disease - Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; Janka, Rolf Matthias; et al. (Hypertension, 2018)
In patients with chronic kidney disease, data on blood pressure (BP) pattern and its association with target organ damage, which indicates elevated cardiovascular risk, are sparse. In 305 treated hypertensive chronic kidney disease patients, we assessed BP pattern, left ventricular mass (magnetic resonance imaging), intima-media thickness (ultrasound), 24-hour-pulse wave velocity and 24-hour-central augmentation index (Mobil-O-Graph). Controlled hypertension (normal office and ambulatory BP) was found in 41% and sustained uncontrolled hypertension (elevated office and ambulatory BP) in 30% of patients. Misclassification of BP status occurred in 29%: white coat uncontrolled hypertension (elevated office but normal ambulatory BP) was detected in 11% and masked uncontrolled hypertension (normal office but elevated ambulatory BP) in 18% of patients. Left ventricular mass was increased in white coat uncontrolled hypertension (+11.2 g), masked uncontrolled hypertension (+9.4 g), and sustained uncontrolled hypertension (+16.6 g) compared with controlled hypertension. Intima-media thickness was similar across all 4 BP groups. Twenty-four hour-pulse wave velocity and 24-hour-central augmentation index were increased in masked uncontrolled hypertension (+0.5 m/sec and +2.5%) and sustained uncontrolled hypertension (+0.5 m/sec and +2.9%) compared with controlled hypertension. In conclusion, based on office BP measurements, misclassification of true BP status occurred in almost one-third of chronic kidney disease patients. Both types of misclassification (white coat uncontrolled hypertension and masked uncontrolled hypertension) were associated with parameters of target organ damage. Ambulatory BP monitoring should be used routinely to identify chronic kidney disease patients at high cardiovascular risk.
EVALuna2:34688

Cardiovascular risk due to diabetes mellitus in patients with chronic kidney disease—prospec data from the German Chronic Kidney Disease - Ruhe, Johannes; Nadal, Jennifer; Bärthlein, Barbara; Meiselbach, Heike; Schultheiss, Ulla T.; Kotsis, Fruzsina; Stockmann, Helena; Krane, Vera; Sommerer, Claudia; Löffler, Ivonne; Saritas, Turgay; Kielstein, Jan T.; et al. (Clinical Kidney Journal, 2023)
Background. Diabetes mellitus (DM) and chronic kidney disease (CKD) are well-known cardiovascular and mortality risk factors. To what extent they act in an additive manner and whether the etiology of CKD modifies the risk is uncertain. Methods. The multicenter, prospective, observational German Chronic Kidney Disease study comprises 5217 participants (1868 with DM) with a baseline mean estimated glomerular filtration rate of 30–60 mL/min/1.73 m2 and/or proteinuria >0.5 g/day. We categorized patients whose CKD was caused by cardiovascular or metabolic diseases (CKDcvm) with and without DM, as opposed to genuine CKD (CKDgen) with and without DM. Recorded outcomes were first events of non-cardiovascular and cardiovascular death, 4-point major adverse cardiovascular events (4-point MACE) and hospitalization for heart failure (HHF). Results. During the 6.5-year follow-up 603 (12%) non-cardiovascular and 209 (4%) cardiovascular deaths, 645 (12%) 4-point MACE, and 398 (8%) HHF were observed, most frequently in patients with DM having CKDcvm. DM increased the risk of non-cardiovascular [hazard ratio (HR) 1.92; 95% confidence interval (CI) 1.59–2.32] and cardiovascular (HR 2.25; 95% CI 1.62–3.12) deaths, 4-point MACE (HR 1.93; 95% CI 1.62–2.31) and HHF (HR 1.87; 95% CI 1.48–2.36). Mortality risks were elevated by DM to a similar extent in CKDcvm and CKDgen, but for HHF in CKDcvm only (HR 2.07; 95% CI 1.55–2.77). In patients with DM, CKDcvm (versus CKDgen) only increased the risk for HHF (HR 1.93; 95% CI 1.15–3.22). Conclusions. DM contributes to cardiovascular and mortality excess risk in patients with moderate to severe CKD in both, CKDcvm and CKDgen. Patients with DM and CKDcvm are particularly susceptible to HHF.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cardiometabolic kidney disease; cardiovascular risk; chronic kidney disease; diabetes mellitus; diabetic kidney disease

Circulating uromodulin inhibits vascular calcification by interfering with pro-inflammatory cytokine signalling - Alesutan, Ioana; Luong, Trang T.D.; Schelski, Nadeshda; Masyout, Jaber; Hille, Susanne; Schneider, Markus; Graham, Delyth; Zickler, Daniel; Verheyen, Nicolas; Estepa, Misael; Pasch, Andreas; Maerz, Winfried; et al. (Cardiovascular Research, 2021)
AIMS: Uromodulin is produced exclusively in the kidney and secreted into both urine and blood. Serum levels of uromodulin are correlated with kidney function and reduced in chronic kidney disease (CKD) patients, but physiological functions of serum uromodulin are still elusive. This study investigated the role of uromodulin in medial vascular calcification, a key factor associated with cardiovascular events and mortality in CKD patients. METHODS AND RESULTS : Experiments were performed in primary human (HAoSMCs) and mouse (MOVAS) aortic smooth muscle cells, cholecalciferol overload and subtotal nephrectomy mouse models and serum from CKD patients. In three independent cohorts of CKD patients, serum uromodulin concentrations were inversely correlated with serum calcification propensity. Uromodulin supplementation reduced phosphate-induced osteo-/chondrogenic transdifferentiation and calcification of HAoSMCs. In human serum, pro-inflammatory cytokines tumour necrosis factor α (TNFα) and interleukin-1β (IL-1β) co-immunoprecipitated with uromodulin. Uromodulin inhibited TNFα and IL-1β-induced osteo-/chondrogenic signalling and activation of the transcription factor nuclear factor kappa-light-chain-enhancer of activated β cells (NF-kB) as well as phosphate-induced NF-kB-dependent transcriptional activity in HAoSMCs. In vivo, adeno-associated virus (AAV)-mediated overexpression of uromodulin ameliorated vascular calcification in mice with cholecalciferol overload. Conversely, cholecalciferol overload-induced vascular calcification was aggravated in uromodulin-deficient mice. In contrast, uromodulin overexpression failed to reduce vascular calcification during renal failure in mice. Carbamylated uromodulin was detected in serum of CKD patients and uromodulin carbamylation inhibited its anti-calcific properties in vitro. CONCLUSIONS : Uromodulin counteracts vascular osteo-/chondrogenic transdifferentiation and calcification, at least in part, through interference with cytokine-dependent pro-calcific signalling. In CKD, reduction and carbamylation of uromodulin may contribute to vascular pathology.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Osteo-/chondrogenic transdifferentiation; Phosphate; Uromodulin; Vascular calcification; Vascular smooth muscle cells

Copeptin, Natriuretic Peptides, and Cardiovascular Outcomes in Patients With CKD: The German Chronic Kidney Disease (GCKD) Study - Schneider, Markus; Schmid, Matthias; Nadal, Jennifer; Krane, Vera; Saritas, Turgay; Busch, Martin; Schultheiss, Ulla T.; Meiselbach, Heike; Friedrich, Nele; Nauck, Matthias; Floege, Jürgen; Kronenberg, Florian; et al. (Kidney Medicine, 2023)
Rationale & Objective: Copeptin and Midrange pro-atrial natriuretic peptide (MR-pro-ANP) are associated with outcomes independently of N-terminal pro-brain natriuretic peptide (NT-pro-BNP) in patients with heart failure (HF). The value of these markers in patients with chronic kidney disease (CKD) has not been studied. Study Design: Prospective cohort study. Setting & Participants: A total of 4,417 patients enrolled in the German Chronic Kidney Disease (GCKD) study with an estimated glomerular filtration rate of 30-60 mL/min/1.73m2 or overt proteinuria (urinary albumin-creatinine ratio >300mg/g or equivalent). Exposures: Copeptin, MR-pro-ANP, and NT-pro-BNP levels were measured in baseline samples. Outcomes: Noncardiovascular death, cardiovascular (CV) death, major adverse CV event (MACE), and hospitalization for HF. Analytical Approach: HRs for associations of Copeptin, MR-pro-ANP, and NT-pro-BNP with outcomes were estimated using Cox regression analyses adjusted for established risk factors. Results: During a maximum follow-up of 6.5 years, 413 non-CV deaths, 179 CV deaths, 519 MACE, and 388 hospitalizations for HF were observed. In Cox regression analyses adjusted for established risk factors, each one of the 3 markers were associated with all the 4 outcomes, albeit the highest HRs were found for NT-pro-BNP. When models were extended to include all the 3 markers, NT-pro-BNP remained associated with all 4 outcomes. Conversely, from the 2 novel markers, associations remained only for Copeptin with non-CV death (HR, 1.62; 95% CI, 1.04-2.54 for highest vs lowest quintile) and with hospitalizations for HF (HR, 1.73; 95% CI, 1.08-2.75). Limitations: Single-point measurements of Copeptin, MR-pro-ANP, and NT-pro-BNP. Conclusions: In patients with moderately severe CKD, we confirm NT-pro-BNP to be strongly associated with all outcomes examined. As the main finding, the novel marker Copeptin demonstrated independent associations with non-CV death and hospitalizations for HF, and should therefore be evaluated further for risk assessment in CKD. Plain-Language Summary: A blood sample–based biomarker that indicates high cardiovascular risk in a patient with kidney disease would help to guide interventions and has the potential to improve outcomes. In 4,417 patients of the German Chronic Kidney Disease study, we assessed the relationship of Copeptin, pro-atrial natriuretic peptide, and N-terminal pro-brain natriuretic peptide (NT-pro-BNP) with important outcomes over a follow-up period of 6.5 years. NT-pro-BNP was strongly associated with all of the 4 outcomes, including death unrelated to cardiovascular disease, death because of cardiovascular disease, a major cardiovascular event, and hospitalization for heart failure. Copeptin was associated with death unrelated to cardiovascular disease and hospitalization for heart failure. NT-pro-BNP and Copeptin are, therefore, promising candidates for a blood sample–based strategy to identify patients with kidney disease at high cardiovascular risk.
CRIS-Team Scopus Importer:2023-10-27
Keywords: biomarkers; cardiac diseases; chronic kidney disease; Copeptin; heart failure; kidney diseases; MR-pro-ANP; NT-pro-BNP

Correction: Blood pressure control in chronic kidney disease: A cross-sectional analysis from the German Chronic Kidney Disease (GCKD) study - Schneider, Markus; Hilgers, Karl Friedrich; Schmid, Matthias; Hübner, Silvia; Nadal, Jennifer; Seitz, David; Busch, Martin; Haller, Hermann; Köttgen, Anna; Kronenberg, Florian; Baid-Agrawal, Seema; Schlieper, Georg; et al. (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0202604.].
EVALuna2:205518

Design and cohort characteristics of TRACK, a prospective study of hyperkalaemia management decision-making - Hsia, Judith; Shivappa, Nitin; Bakhai, Ameet; Bover, Jordi; Butler, Javed; Ferraro, Pietro Manuel; Fried, Linda; Schneider, Markus; Tangri, Navdeep; Winkelmayer, Wolfgang C.; Bishop, Meredith; Chen, Hungta; et al. (Clinical Kidney Journal, 2024)
Background. Guideline-recommended hyperkalaemia management includes dietary potassium (K+) restriction, bicarbonate correction, diuretics and K+ binders with dose reduction of renin–angiotensin–aldosterone system inhibitors as a last resort. The extent to which these recommendations are implemented is uncertain, as real-world data on hyperkalaemia management are limited. The Tracking Treatment Pathways in Adult Patients with Hyperkalemia (TRACK) study is a multinational, prospective, longitudinal study that is being conducted to address this knowledge gap. We report the design and baseline cohort characteristics of this real-world study of hyperkalaemia management decision-making. Methods. This study enrolled participants within 21 days of an episode of hyperkalaemia in four European countries (UK, Spain, Germany, Italy) and the USA. During the 12-month follow up, data collected will include participant and healthcare provider characteristics (specialty and practice setting), hyperkalaemia treatment objectives and strategies, rationale for management decisions and indicators of response and patient-reported perceptions of their hyperkalaemia treatment. Results. The enrolled cohort includes 1330 participants, mean age 68 years, of whom 31% were women. At baseline, 6% reported heart failure, 55% chronic kidney disease, 29% both and 9% neither. Most participants (57%) were taking an angiotensin-converting enzyme inhibitor, angiotensin receptor blocker or angiotensin receptor/neprilysin inhibitor at baseline. Mineralocorticoid receptor antagonist use was lower (14%). Conclusions. The prospective TRACK study will shed light on practitioners’ hyperkalaemia management decision-making and assess the impact of their decisions on hyperkalaemia recurrence. Understanding practitioners’ underlying thought processes will facilitate efforts to improve hyperkalaemia management. ClinicalTrials.gov: NCT05408039
CRIS-Team Scopus Importer:2024-11-08
Keywords: chronic kidney disease; heart failure; hyperkalaemia management; RAASi; real-world evidence

Differential Prognostic Utility of Adiposity Measures in Chronic Kidney Disease - Cejka, Vladimir; Störk, Stefan; Nadal, Jennifer; Schmid, Matthias; Sommerer, Claudia; Sitter, Thomas; Meiselbach, Heike; Busch, Martin; Schneider, Markus; Saritas, Turgay; Schultheiss, Ulla T.; Kotsis, Fruzsina; et al. (Journal of Renal Nutrition, 2023)
Objective: Adipose tissue contributes to adverse outcomes in chronic kidney disease (CKD), but there is uncertainty regarding the prognostic relevance of different adiposity measures. We analyzed the associations of neck circumference (NC), waist circumference (WC), and body mass index (BMI) with clinical outcomes in patients with mild to severe CKD. Methods: The German Chronic Kidney Disease study is a prospective cohort study, which enrolled Caucasian adults with mild to severe CKD, defined as estimated glomerular filtration rate : 30-60 mL/min/1.73 m2, or >60 mL/min/1.73 m2 in the presence of overt proteinuria. Associations of NC, WC, and BMI with all-cause death, major adverse cardiovascular events (MACE: a composite of nonfatal stroke, nonfatal myocardial infarction, peripheral artery disease intervention, and cardiovascular death), and kidney failure (a composite of dialysis or transplantation) were analyzed using multivariable Cox proportional hazards regression models adjusted for confounders and the Akaike information criteria were calculated. Models included sex interactions with adiposity measures. Results: A total of 4537 participants (59% male) were included in the analysis. During a 6.5-year follow-up, 339 participants died, 510 experienced MACE, and 341 developed kidney failure. In fully adjusted models, NC was associated with all-cause death in women (hazard ratio 1.080 per cm; 95% CI 1.009-1.155) but not in men. Irrespective of sex, WC was associated with all-cause death (hazard ratio 1.014 per cm; 95% CI 1.005-1.038). NC and WC showed no association with MACE or kidney failure. BMI was not associated with any of the analyzed outcomes. Models of all-cause death, including WC offered the best (lowest) Akaike information criteria. Conclusion: In Caucasian patients with mild to severe CKD, higher NC (in women) and WC were significantly associated with increased risk of death from any cause but BMI was not.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adiposity; body Mass Index; chronic kidney disease; mortality; neck circumference; waist circumference

Educational Attainment Is Associated With Kidney and Cardiovascular Outcomes in the German CKD (GCKD) Cohort - Winitzki, Doris; Zacharias, Helena U.; Nadal, Jennifer; Baid-Agrawal, Seema; Schaeffner, Elke; Schmid, Matthias; Busch, Martin; Bergmann, Manuela M.; Schultheiss, Ulla; Kotsis, Fruzsina; Stockmann, Helena; Meiselbach, Heike; et al. (Kidney International Reports, 2022)
Introduction: Prospective data on impact of educational attainment on prognosis in patients with chronic kidney disease (CKD) are scarce. We investigated the association between educational attainment and all-cause mortality, major adverse cardiovascular (CV) events (MACEs), kidney failure requiring dialysis, and CKD etiology. Methods: Participants (N = 5095, aged 18–74 years) of the ongoing multicenter German Chronic Kidney Disease (GCKD) cohort, enrolled on the basis of an estimated glomerular filtration rate (eGFR) of 30 to 60 ml/min (stages G3, A1–A3) or overt proteinuria (stages G1–G2, A3), were divided into 3 categories according to their educational attainment and were followed for 6.5 years. Results: Participants with low educational attainment (vs. high) had a higher risk for mortality (hazard ratio [HR] 1.48, 95% CI: 1.16–1.90), MACE (HR 1.37, 95% CI: 1.02–1.83), and kidney failure (HR 1.54, 95% CI: 1.15–2.05). Mediators between low educational attainment and mortality were smoking, CV disease (CVD) at baseline, low income, higher body mass index, and higher serum levels of CRP, high-density lipoprotein cholesterol, uric acid, NGAL, BAP, NT-proBNP, OPN, H-FABP, and urea. Low educational attainment was positively associated with diabetic nephropathy (odds ratio [OR] 1.65, 95% CI: 1.36–2.0) and CKD subsequent to acute kidney injury (OR 1.56, 95% CI: 1.03–2.35), but negatively associated with IgA nephropathy (OR 0.68, 95% CI: 0.52–0.90). Conclusion: Low educational attainment is associated with adverse outcomes and CKD etiology. Lifestyle habits and biomarkers mediate associations between low educational attainment and mortality. Recognition of the role of educational attainment and the associated health-relevant risk factors is important to optimize the care of patients with CKD and improve prognosis.
CRIS-Team Scopus Importer:2022-03-11
Keywords: biomarker; CASMIN; chronic kidney disease; CKD; educational attainment; socioeconomic status

Effects of the Selective Sodium-Glucose Cotransporter 2 Inhibitor Empagliflozin on Vascular Function and Central Hemodynamics in Patients With Type 2 Diabetes Mellitus - Striepe, Kristina; Jumar, Agnes; Ott, Christian; Karg, Margarete; Schneider, Markus; Kannenkeril, Dennis; Schmieder, Roland (Circulation, 2017)
EVALuna2:4021

Epicardial fat, cardiovascular risk factors and calcifications in patients with chronic kidney disease - Saritas, Turgay; Reinartz, Sebastian Daniel; Nadal, Jennifer; Schmoee, Jonas; Schmid, Matthias; Achenbach, Stephan; Stoerk, Stefan; Wanner, Christoph; Floege, Jurgen; Schneider, Markus; Schlieper, Georg; Marwan, Mohamed; et al. (Clinical Kidney Journal, 2020)
Background. Epicardial adipose tissue (EAT) exerts cardiopathogenic effects, but the independent association between EAT and cardiovascular (CV) calcification in patients with chronic kidney disease (CKD) remains controversial. We therefore assessed the association between EAT, CV risk factors and CV calcifications.
CRIS-Team WoS Importer:2020-10-30

Heart-Type Fatty Acid Binding Protein, Cardiovascular Outcomes, and Death: Findings From the German CKD Cohort Study - Schneider, Markus; Schmid, Matthias; Nadal, Jennifer; Wanner, Christoph; Krane, Vera; Floege, Jürgen; Saritas, Turgay; Busch, Martin; Sitter, Thomas; Friedrich, Nele; Stockmann, Helena; Meiselbach, Heike; et al. (American Journal of Kidney Diseases, 2022)
Rationale & Objective: Heart-type fatty acid binding protein (H-FABP) is a biomarker that has been shown to provide long-term prognostic information in patients with coronary artery disease independently of high-sensitivity troponin T (hs-TNT). We examined the independent associations of H-FABP with cardiovascular outcomes in patients with chronic kidney disease (CKD). Study Design: Prospective cohort study. Setting & Participants: 4,951 patients enrolled in the German Chronic Kidney Disease (GCKD) study with an estimated glomerular filtration rate of 30-60 mL/min/1.73 m2 or overt proteinuria (urinary albumin-creatinine ratio > 300 mg/g or equivalent). Exposure: Serum levels of H-FABP and hs-TNT were measured at study entry. Outcome: Noncardiovascular (non-CV) death, CV death, combined major adverse CV events (MACE), and hospitalization for congestive heart failure (CHF). Analytical Approach: Hazard ratios (HRs) for associations of H-FABP and hs-TNT with outcomes were estimated using Cox regression analyses adjusted for established risk factors. Results: During a maximum follow-up of 6.5 years, 579 non-CV deaths, 190 CV deaths, 522 MACE, and 381 CHF hospitalizations were observed. In Cox regression analyses adjusted for established risk factors, H-FABP was associated with all 4 outcomes, albeit with lower HRs than those found for hs-TNT. After further adjustment for hs-TNT levels, H-FABP was found to be associated with non-CV death (HR, 1.57 [95% CI, 1.14-2.18]) and MACE (HR, 1.40 [95% CI, 1.02-1.92]) but with neither CV death (HR, 1.64 [95% CI, 0.90-2.99]) nor CHF hospitalizations (HR, 1.02 [95% CI, 0.70-1.49]). Limitations: Single-point measurements of H-FABP and hs-TNT. Uncertain generalizability to non-European populations. Conclusions: In this large cohort of patients with CKD, H-FABP was associated with non-CV death and MACE, even after adjustment for hs-TNT. Whether measurement of H-FABP improves cardiovascular disease risk prediction in these patients warrants further studies.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Biomarkers; cardiac death; cardiac diseases; cardiovascular disease (CVD); chronic kidney disease (CKD); heart failure; heart type fatty acid binding protein (H-FABP); high-sensitivity troponin T (hs-TNT); kidney diseases; prognosis; renal function

How to Retard Progression of Chronic Kidney Disease - Schneider, Markus; Hilgers, Karl Friedrich (Deutsche Medizinische Wochenschrift, 2017)
End stage chronic kidney disease (CKD) requiring renal replacement therapy is related to poor quality of life and high mortality. Thus, slowing the progression of CKD is an important purpose of therapy. Some general therapeutic approaches aim to slow the decline of renal function and they can be applied in all patients with CKD - irrespective of the underlying cause of CKD. A key intervention is lowering blood pressure (target: <= 140/90 mmHg, and in patients with albuminuria <= 130/80 mmHg). Inhibitors of the renin angiotensin system preferentially should be used in case of albuminuria, depending on the diabetic status and the level of albuminuria: in diabetics with albuminuria >= 30 mg/d, in non-diabetics with albuminuria > 300 mg/d. Mineralocorticoid receptor blockers and endothelin receptors blockers promise novel anti-proteinuric strategies - but still validation of their positive effects on retarding CKD progression is necessary. In patients with diabetic kidney disease, glycemic control aiming for an HbA1c of ? 7.0 % has been established to slow CKD progression. Furthermore, SGLT-2 inhibition with empagliflozin may be considered as a new therapeutic approach that provides additional cardiovascular and renal protection. Finally, recent studies suggest: correction of metabolic acidosis and avoidance of episodes of acute renal failure may provide protection against the progression of CKD.
EVALuna2:4025

Impact of C-reactive protein on osteo-/chondrogenic transdifferentiation and calcification of vascular smooth muscle cells - Henze, Laura A.; Luong, Trang T.D.; Boehme, Beate; Masyout, Jaber; Schneider, Markus; Brachs, Sebastian; Lang, Florian; Pieske, Burkert; Pasch, Andreas; Eckardt, Kai-Uwe; Voelkl, Jakob; Alesutan, Ioana (Aging-Us, 2019)
Medial vascular calcification occurs during the aging process and is strongly accelerated by chronic kidney disease (CKD). Elevated C-reactive protein (CRP) levels are associated with vascular calcification, cardiovascular events and mortality in CKD patients. CRP is an important promoter of vascular inflammation. Inflammatory processes are critically involved in initiation and progression of vascular calcification. Thus, the present study explored a possible impact of CRP on vascular calcification. We found that CRP promoted osteo-/chondrogenic transdifferentiation and aggravated phosphate-induced osteo-/chondrogenic transdifferentiation and calcification of primary human aortic smooth muscle cells (HAoSMCs). These effects were paralleled by increased cellular oxidative stress and corresponding pro-calcific downstream-signaling. Antioxidants or p38 MAPK inhibition suppressed CRP-induced osteo-/chondrogenic signaling and mineralization. Furthermore, silencing of Fc fragment of IgG receptor IIa (FCGR2A) blunted the pro-calcific effects of CRP. Vascular CRP expression was increased in the klotho-hypomorphic mouse model of aging as well as in HAoSMCs during calcifying conditions. In conclusion, CRP augments osteo-/chondrogenic transdifferentiation of vascular smooth muscle cells through mechanisms involving FCGR2A-dependent induction of oxidative stress. Thus, systemic inflammation may actively contribute to the progression of vascular calcification.
CRIS-Team Scopus Importer:2019-08-30
Keywords: CKD; CRP; Osteo-/chondrogenic signaling; Oxidative stress; Vascular calcification; Vascular smooth muscle cells

Incorporating kidney disease measures into cardiovascular risk prediction: Development and validation in 9 million adults from 72 datasets - Matsushita, Kunihiro; Jassal, Simerjot K.; Sang, Yingying; Ballew, Shoshana H.; Grams, Morgan E.; Surapaneni, Aditya; Arnlov, Johan; Bansal, Nisha; Bozic, Milica; Brenner, Hermann; Brunskill, Nigel J.; Chang, Alex R.; et al. (EClinicalMedicine, 2020)
Background: Chronic kidney disease (CKD) measures (estimated glomerular filtration rate [eGFR] and albuminuria) are frequently assessed in clinical practice and improve the prediction of incident cardiovascular disease (CVD), yet most major clinical guidelines do not have a standardized approach for incorporating these measures into CVD risk prediction. “CKD Patch” is a validated method to calibrate and improve the predicted risk from established equations according to CKD measures. Methods: Utilizing data from 4,143,535 adults from 35 datasets, we developed several “CKD Patches” incorporating eGFR and albuminuria, to enhance prediction of risk of atherosclerotic CVD (ASCVD) by the Pooled Cohort Equation (PCE) and CVD mortality by Systematic COronary Risk Evaluation (SCORE). The risk enhancement by CKD Patch was determined by the deviation between individual CKD measures and the values expected from their traditional CVD risk factors and the hazard ratios for eGFR and albuminuria. We then validated this approach among 4,932,824 adults from 37 independent datasets, comparing the original PCE and SCORE equations (recalibrated in each dataset) to those with addition of CKD Patch. Findings: We confirmed the prediction improvement with the CKD Patch for CVD mortality beyond SCORE and ASCVD beyond PCE in validation datasets (Δc-statistic 0.027 [95% CI 0.018–0.036] and 0.010 [0.007–0.013] and categorical net reclassification improvement 0.080 [0.032–0.127] and 0.056 [0.044–0.067], respectively). The median (IQI) of the ratio of predicted risk for CVD mortality with CKD Patch vs. the original prediction with SCORE was 2.64 (1.89–3.40) in very high-risk CKD (e.g., eGFR 30–44 ml/min/1.73m2 with albuminuria ≥30 mg/g), 1.86 (1.48–2.44) in high-risk CKD (e.g., eGFR 45–59 ml/min/1.73m2 with albuminuria 30–299 mg/g), and 1.37 (1.14–1.69) in moderate risk CKD (e.g., eGFR 60–89 ml/min/1.73m2 with albuminuria 30–299 mg/g), indicating considerable risk underestimation in CKD with SCORE. The corresponding estimates for ASCVD with PCE were 1.55 (1.37–1.81), 1.24 (1.10–1.54), and 1.21 (0.98–1.46). Interpretation: The “CKD Patch” can be used to quantitatively enhance ASCVD and CVD mortality risk prediction equations recommended in major US and European guidelines according to CKD measures, when available. Funding: US National Kidney Foundation and the NIDDK.
CRIS-Team Scopus Importer:2020-11-06
Keywords: cardiovascular disease; Chronic kidney disease; meta-analysis; risk prediction

Interactive exploration of adverse events and multimorbidity in CKD. - Steinbrenner, Inga; Kotsis, Fruzsina; Kosch, Robin; Meiselbach, Heike; Bärthlein, Barbara; Stockmann, Helena; Lipovsek, Jan; Zacharias, Helena U.; Altenbuchinger, Michael; Dienemann, Thomas; Wytopil, Monika; Bächle, Helena; et al. (Nephrology Dialysis Transplantation, 2024)
BACKGROUND: Persons with chronic kidney disease (CKD) are at increased risk of adverse events, early mortality and multimorbidity. A detailed overview of adverse event types and rates from a large CKD cohort under regular nephrological care is missing. We generated an interactive tool to enable exploration of adverse events and their combinations in the prospective, observational German CKD (GCKD) study. METHODS: The GCKD study enrolled 5217 participants under regular nephrological care with an estimated glomerular filtration rate of 30-60 or >60 mL/min/1.73 m2 and an overt proteinuria. Cardiovascular, cerebrovascular and peripheral vascular, kidney, infection, and cancer events, as well as deaths were adjudicated following a standard operation procedure. We summarized these time-to-event data points for exploration in interactive graphs within an R shiny app. Multivariable adjusted Cox models for time to first event were fitted. Cumulative incidence functions, Kaplan-Meier curves and intersection plots were used to display main adverse events and their combinations by sex and CKD etiology. RESULTS: Over a median of 6.5 years, 10 271 events occurred in 2947 participants (56.5%), of which 680 participants (13.0%) died. The new publicly available interactive platform enables readers to scrutinize adverse events and their combinations as well as mortality trends as a gateway to better understand multimorbidity in CKD: incident rates per 1000 patient-years varied by event type, CKD etiology and baseline characteristics. Incidence rates for the most frequent events and their recurrence were 113.6 (cardiovascular), 75.0 (kidney) and 66.0 (infection). Participants with presumed diabetic kidney disease and men were more prone to experiencing events. CONCLUSION: This comprehensive explorative tool to visualize adverse events (https://www.gckd.org/studienhintergrund/previous-study-results/event-analysis/), their combination, mortality and multimorbidity among persons with CKD may serve as a valuable resourec for patient care, identification of high-risk groups, health services and public health policy planning.
EVALuna2:576249

Left Ventricular Structure in Patients With Mild-to-Moderate CKD-a Magnetic Resonance Imaging Study - Schneider, Markus; Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; et al. (Kidney International Reports, 2019)
Introduction: The high burden of left ventricular (LV) abnormalities in patients with advanced chronic kidney disease (CKD) is well established. However, less is known about the prevalence, patterns, and determinants of LV abnormalities in patients with early CKD.
CRIS-Team WoS Importer:2019-02-21

Low adherence to CKD-specific dietary recommendations associates with impaired kidney function, dyslipidemia, and inflammation - Kaesler, Nadine; Baid-Agrawal, Seema; Grams, Sabine; Nadal, Jennifer; Schmid, Matthias; Schneider, Markus; Eckardt, Kai-Uwe; Floege, Jürgen; Bergmann, Manuela M.; Schlieper, Georg; Saritas, Turgay (European Journal of Clinical Nutrition, 2021)
Background/Objectives: A diet following chronic kidney disease (CKD)-specific recommendations is considered essential for optimal management of patients with CKD. However, data on the adherence to these recommendations and its implications for health-relevant biomarkers are lacking. The objectives were to estimate adherence to CKD-specific dietary recommendations, to identify characteristics and lifestyle variables associated with poor adherence, and to investigate the relationship of adherence with biomarkers. Methods: In this cross-sectional analysis, average dietary intake was estimated in 3193 participants with moderately severe CKD enrolled into the observational multicenter German CKD study using a food frequency questionnaire. A CKD diet score was developed to assess adherence to CKD-specific dietary recommendations based on intake of sodium, potassium, fiber, protein, sugar, and cholesterol. The associations of dietary adherence with characteristics, lifestyle variables, and biomarker levels were determined. Results: Logistic regression analysis revealed younger age, higher body mass index, male gender, lower educational attainment, various lifestyle variables (cigarette smoking, infrequent alcohol consumption, low physical activity), and lower estimated glomerular filtrate rate associated with lower adherence to dietary recommendations. Low adherence to dietary recommendations was further associated with dyslipidemia, higher uric acid, and C-reactive protein levels. Associations between low dietary adherence and biomarkers were mostly driven by low intake of fiber and potassium, and high intake of sugar and cholesterol. Conclusions: This study revealed differential characteristics and biomarkers associated with lower adherence to CKD-specific dietary recommendations. Promotion of CKD-specific dietary recommendations may help to mitigate the adverse prognosis in CKD patients.
CRIS-Team Scopus Importer:2021-02-12

Low-dose eplerenone decreases left ventricular mass in treatment-resistant hypertension - Schneider, Andreas; Schwab, Johannes; Karg, Margarete; Kalizki, Tatjana; Reinold, Annemarie; Schneider, Markus; Schmieder, Roland; Schmidt, Bernhard M. W. (Journal of Hypertension, 2017)
Mineralocorticoid receptor antagonists are increasingly used in patients with treatment-resistant hypertension (TRH). There is experimental evidence for blood pressure (BP) independent effects of mineralocorticoid receptor blockade on cardiovascular target organ damage. We hypothesized that low-dose eplerenone (50 mg) will reduce left ventricular mass (LVM) beyond its BP-lowering effects.We performed a randomized, double-blind, placebo-controlled, parallel group study in 51 patients with TRH. Patients were allocated to receive either eplerenone 50 mg or placebo for 6 months, while other antihypertensive agents could be added in both groups to achieve a BP target of less than 140/90 mmHg. LVM was assessed by MRI before and after treatment.Baseline office BP was similar in the eplerenone and the placebo group (166 ± 21/91 ± 15 versus 159 ± 19/94 ± 8 mmHg, n.s.). BP was similarly reduced in the eplerenone versus the placebo group (-35 ± 20/-15 ± 11 versus -30 ± 19/-13 ± 7 mmHg, n.s.). However, LVM was reduced only in the eplerenone group (from 155 ± 33 to 136 ± 33 g, P < 0.001), but not in the placebo group (152 ± 32 versus 148 ± 38 g, P = 0.45).Despite similar BP-lowering, only patients with TRH who were allocated to eplerenone experienced a reduction of LVM. Thus, our data suggest that in patients with TRH, mineralocorticoid receptor antagonists should be used preferentially in order to achieve an effective reduction of LVM along with the improvement of BP control.
EVALuna2:3937

Major cardiovascular events and subsequent risk of kidney failure with replacement therapy: a CKD Prognosis Consortium study - Mark, Patrick B.; Carrero, Juan J.; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H.; Grams, Morgan E.; Coresh, Josef; Surapaneni, Aditya; Brunskill, Nigel J.; Chalmers, John; Chan, Lili; Chang, Alex R.; et al. (European Heart Journal, 2023)
Aims Chronic kidney disease (CKD) increases risk of cardiovascular disease (CVD). Less is known about how CVD associates with future risk of kidney failure with replacement therapy (KFRT). Methods and results The study included 25 903 761 individuals from the CKD Prognosis Consortium with known baseline estimated glomerular filtration rate (eGFR) and evaluated the impact of prevalent and incident coronary heart disease (CHD), stroke, heart failure (HF), and atrial fibrillation (AF) events as time-varying exposures on KFRT outcomes. Mean age was 53 (standard deviation 17) years and mean eGFR was 89 mL/min/1.73 m(2), 15% had diabetes and 8.4% had urinary albumin-to-creatinine ratio (ACR) available (median 13 mg/g); 9.5% had prevalent CHD, 3.2% prior stroke, 3.3% HF, and 4.4% prior AF. During follow-up, there were 269 142 CHD, 311 021 stroke, 712 556 HF, and 605 596 AF incident events and 101 044 (0.4%) patients experienced KFRT. Both prevalent and incident CVD were associated with subsequent KFRT with adjusted hazard ratios (HRs) of 3.1 [95% confidence interval (CI): 2.9-3.3], 2.0 (1.9-2.1), 4.5 (4.2-4.9), 2.8 (2.7-3.1) after incident CHD, stroke, HF and AF, respectively. HRs were highest in first 3 months post-CVD incidence declining to baseline after 3 years. Incident HF hospitalizations showed the strongest association with KFRT [HR 46 (95% CI: 43-50) within 3 months] after adjustment for other CVD subtype incidence. Conclusion Incident CVD events strongly and independently associate with future KFRT risk, most notably after HF, then CHD, stroke, and AF. Optimal strategies for addressing the dramatic risk of KFRT following CVD events are needed.
CRIS-Team WoS Importer:2023-02-24

Mitochondrial DNA copy number is associated with mortality and infections in a large cohort of patients with chronic kidney disease - Fazzini, Federica; Lamina, Claudia; Fendt, Liane; Schultheiss, Ulla T.; Kotsis, Fruzsina; Hicks, Andrew A.; Meiselbach, Heike; Weissensteiner, Hansi; Forer, Lukas; Krane, Vera; Eckardt, Kai-Uwe; Köttgen, Anna; et al. (Kidney International, 2019)
Damage of mitochondrial DNA (mtDNA) with reduction in copy number has been proposed as a biomarker for mitochondrial dysfunction and oxidative stress. Chronic kidney disease (CKD) is associated with increased mortality and risk of cardiovascular disease, but the underlying mechanisms remain incompletely understood. Here we investigated the prognostic role of mtDNA copy number for cause-specific mortality in 4812 patients from the German Chronic Kidney Disease study, an ongoing prospective observational national cohort study of patients with CKD stage G3 and A1-3 or G1-2 with overt proteinuria (A3) at enrollment. MtDNA was quantified in whole blood using a plasmid-normalized PCR-based assay. At baseline, 1235 patients had prevalent cardiovascular disease. These patients had a significantly lower mtDNA copy number than patients without cardiovascular disease (fully-adjusted model: odds ratio 1.03, 95% confidence interval [CI] 1.01-1.05 per 10 mtDNA copies decrease). After four years of follow-up, we observed a significant inverse association between mtDNA copy number and all-cause mortality, adjusted for kidney function and cardiovascular disease risk factors (hazard ratio 1.37, 95% CI 1.09-1.73 for quartile 1 compared to quartiles 2-4). When grouped by causes of death, estimates pointed in the same direction for all causes but in a fully-adjusted model decreased copy numbers were significantly lower only in infection-related death (hazard ratio 1.82, 95% CI 1.08-3.08). A similar association was observed for hospitalizations due to infections in 644 patients (hazard ratio 1.19, 95% CI 1.00-1.42 in the fully-adjusted model). Thus, our data support a role of mitochondrial dysfunction in increased cardiovascular disease and mortality risks as well as susceptibility to infections in patients with CKD.
CRIS-Team Scopus Importer:2019-07-02
Keywords: chronic kidney disease; infections; mitochondrial DNA copy number; mortality

Novel Biomarkers in Patients with Chronic Kidney Disease: An Analysis of Patients Enrolled in the GCKD-Study - Mirna, Moritz; Topf, Albert; Wernly, Bernhard; Rezar, Richard; Paar, Vera; Jung, Christian; Salmhofer, Hermann; Kopp, Kristen; Hoppe, Uta C.; Schulze, P. Christian; Kretzschmar, Daniel; Schneider, Markus; et al. (Journal of Clinical Medicine, 2020)
Background: Chronic kidney disease (CKD) and cardiovascular diseases (CVD) often occur concomitantly, and CKD is a major risk factor for cardiovascular mortality. Since some of the most commonly used biomarkers in CVD are permanently elevated in patients with CKD, novel biomarkers are warranted for clinical practice. Methods: Plasma concentrations of five cardiovascular biomarkers (soluble suppression of tumorigenicity (sST2), growth differentiation factor 15 (GDF-15), heart-type fatty acid-binding protein (H-FABP), insulin-like growth factor-binding protein 2 (IGF-BP2), and soluble urokinase plasminogen activator receptor) were analyzed by means of enzyme-linked immunosorbent assay (ELISA) in 219 patients with CKD enrolled in the German Chronic Kidney Disease (GCKD) study. Results: Except for sST2, all of the investigated biomarkers were significantly elevated in patients with CKD (2.0- to 4.4-fold increase in advanced CKD (estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m(2) body surface area (BSA)) and showed a significant inverse correlation with eGFR. Moreover, all but H-FABP and sST2 were additionally elevated in patients with micro- and macro-albuminuria. Conclusions: Based on our findings, sST2 appears to be the biomarker whose diagnostic performance is least affected by decreased renal function, thus suggesting potential viability in the management of patients with CVD and concomitant CKD. The predictive potential of sST2 remains to be proven in endpoint studies.
CRIS-Team WoS Importer:2020-05-08

OSTEOPONTIN AND ITS ASSOCIATION WITH ADVERSE EVENTS IN THE GERMAN CHRONIC KIDNEY DISEASE STUDY - Steinbrenner, Inga; Cheng, Yurong; Nadal, Jennifer; Schmid, Matthias; Kotsis, Fruzsina Kinga; Meiselbach, Heike; Schneider, Markus; Krane, Vera; Nauck, Matthias; Eckardt, Kai-Uwe; Koettgen, Anna; Sekula, Peggy; et al. (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Prevalence of undiagnosed stage 3 chronic kidney disease in France, Germany, Italy, Japan and the USA: results from the multinational observational REVEAL-CKD study - Tangri, Navdeep; Moriyama, Toshiki; Schneider, Markus; Virgitti, Jean Blaise; De Nicola, Luca; Arnold, Matthew; Barone, Salvatore; Peach, Emily; Wittbrodt, Eric; Chen, Hungta; Järbrink, Krister; Kushner, Pamela (BMJ Open, 2023)
OBJECTIVES: REVEAL-CKD aims to estimate the prevalence of, and factors associated with, undiagnosed stage 3 chronic kidney disease (CKD). DESIGN: Multinational, observational study. SETTING: Data from six country-specific electronic medical records and/or insurance claims databases from five countries (France, Germany, Italy, Japan and the USA [two databases]). PARTICIPANTS: Eligible participants (≥18 years old) had ≥2 consecutive estimated glomerular filtration rate (eGFR) measurements (calculated from serum creatinine values, sex and age) taken from 2015 onwards that were indicative of stage 3 CKD (≥30 and <60 mL/min/1.73 m2). Undiagnosed cases lacked an International Classification of Diseases 9/10 diagnosis code for CKD (any stage) any time before, and up to 6 months after, the second qualifying eGFR measurement (study index). MAIN OUTCOME MEASURES: The primary outcome was point prevalence of undiagnosed stage 3 CKD. Time to diagnosis was assessed using the Kaplan-Meier approach. Factors associated with lacking a CKD diagnosis and risk of diagnostic delay were assessed using logistic regression adjusted for baseline covariates. RESULTS: The prevalence of undiagnosed stage 3 CKD was 95.5% (19 120/20 012 patients) in France, 84.3% (22 557/26 767) in Germany, 77.0% (50 547/65 676) in Italy, 92.1% (83 693/90 902) in Japan, 61.6% (13 845/22 470) in the US Explorys Linked Claims and Electronic Medical Records Data database and 64.3% (161 254/250 879) in the US TriNetX database. The prevalence of undiagnosed CKD increased with age. Factors associated with undiagnosed CKD were female sex (vs male, range of odds ratios across countries: 1.29-1.77), stage 3a CKD (vs 3b, 1.81-3.66), no medical history (vs a history) of diabetes (1.26-2.77) or hypertension (1.35-1.78). CONCLUSIONS: There are substantial opportunities to improve stage 3 CKD diagnosis, particularly in female patients and older patients. The low diagnosis rates in patients with comorbidities that put them at risk of disease progression and complications require attention. TRIAL REGISTRATION: NCT04847531.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Adult nephrology; Chronic renal failure; EPIDEMIOLOGY; NEPHROLOGY

Prevalence, phenotypic characteristics and prognostic role of apparent treatment resistant hypertension in the German Chronic Kidney Disease (GCKD) study - Mielke, Johanna; Trucks-Jansen, Holger; Schurmann, Claudia; Kotsis, Fruzsina; Koettgen, Anna; Schneider, Markus; Eckardt, Kai-Uwe; Freitag, Daniel F.; Eitner, Frank; Becker, Michael S. (Journal of Human Hypertension, 2022)
Treatment resistant hypertension (TRH) appears of particular relevance in patients with chronic kidney disease (CKD). However, causes and consequences of TRH in CKD patients remain incompletely understood. Therefore, we analyzed the prevalence of apparent TRH (aTRH), and phenotypic characteristics and prognosis associated with aTRH among participants of the German Chronic Kidney Disease (GCKD) study. As insufficient medication adherence has been shown to be a frequent cause of pseudoresistance, we also assessed treatment adherence. Study participants were classified as having aTRH, controlled hypertension and uncontrolled hypertension based on study visit blood pressure and self-reported medication intake. Drug adherence was assessed by comparing self-reported antihypertensive medication with detectable urinary drug metabolites measured by mass spectroscopy. Out of 4901 individuals included in this study, 38% were classified as having aTRH. Male sex, older age, lower estimated glomerular filtration rate (eGFR), higher body mass index (BMI), higher urine albumin-to-creatinine ratio (UACR) and presence of diabetes mellitus were independently associated with higher prevalence of aTRH in a multivariable adjusted regression model. Patients classified as aTRH had higher risk for major adverse cardiovascular events and worsening of kidney disease compared to patients with no aTRH after multivariate adjustment for potential confounders. There was a high agreement between self-reported medication and detectable urinary drug metabolites. In conclusion, in a cohort of Caucasian patients with moderately severe CKD, aTRH was highly prevalent and, in most cases, likely not caused by low medication adherence. Furthermore, aTRH was linked to cardio-renal endpoints, emphasizing the need for improved management.
CRIS-Team WoS Importer:2022-05-20

PROGNOSTIC IMPACT OF NECK CIRCUMFERENCE ON CARDIVASCULAR OUTCOMES AND MORTALITY IN PATIENTS WITH MODERATE CHRONIC KIDNEY DISEASE: AN ANALYSIS FROM THE GERMAN CHRONIC KIDNEY DISEASE (GCKD) STUDY - Cejka, Vladimir; Stoerk, Stefan; Nadal, Jennifer; Schultheiss, Ulla T.; Koettgen, Anna; Sommerer, Claudia; Sitter, Thomas; Meiselbach, Heike; Busch, Martin; Schneider, Markus; Saritas, Turgay; Kotsis, Fruzsina Kinga; et al. (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-09-18

RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM INHIBITOR THERAPY IN PATIENTS WITH CHRONIC KIDNEY DISEASE: AN ANALYSIS FROM THE GERMAN CHRONIC KIDNEY DISEASE STUDY - Schneider, Markus; Meiselbach, Heike; Schulmann, Thierry; Cornea, Georgiana; Eckardt, Kai-Uwe (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-11-26

Retinal capillary and arteriolar changes in patients with chronic kidney disease - Bosch, Agnes; Scheppach, Johannes B.; Harazny, Joanna M.; Raff, Ulrike; Schmieder, Roland; Schneider, Markus; Eckardt, Kai-Uwe (Microvascular Research, 2018)
RATIONALE: Premature cardiovascular disease is a leading cause of death in patients with chronic kidney disease (CKD). In animal models CKD has been shown to cause renal and extrarenal vascular remodeling and capillary rarefaction, but data in humans with CKD are sparse. Retinal arteriolar wall-to-lumen ratio (WLR) is an established marker of early end-organ damage and there is evidence that arteriolar and capillary changes in the retinal circulation mirror those in the general and in particular the cerebrovascular microcirculation. OBJECTIVE: The aim of this study was to compare retinal capillary density and arteriolar structure between patients with CKD and healthy individuals. METHODS: We compared 76 patients with CKD stage 3+ or proteinuria >500 mg/g creatinine in the presence of a normal GFR from the German Chronic Kidney Disease cohort to 53 healthy control subjects, who participated in clinical trials during 2007 and 2015 in our Clinical Research Center. Retinal vascular parameters were measured non-invasively in vivo by scanning laser Doppler Flowmetry (SLDF, Heidelberg Engineering, Germany). Capillary rarefaction was assessed by intercapillary distance. RESULTS: Patients with CKD showed greater WLR (0.403 ± 0.11 vs 0.351 ± 0.11, p = 0.010) and greater wall thickness (WT) (15.1 ± 4.1 vs 13.5 ± 3.8, p = 0.026) compared to healthy individuals. Intercapillary distance (ICD) (22.4 ± 5.7 vs 20.2 ± 4.1, p = 0.008) was greater in the CKD group compared to the healthy control group. After adjustment for differences in clinical characteristics of the groups (age, gender, BMI, serum cholesterol) WLR (p = 0.046), WT (p = 0.025) and ICD (p = 0.003) remained significantly different between the two groups. There was a correlation between serum phosphate level and WLR in the CKD group (r = 0.288, p = 0.013). CONCLUSION: Patients with moderately severe CKD show retinal signs of end-organ damage indicated by an increased wall-to-lumen ratio and capillary rarefaction.
EVALuna2:34237

Risikoscores für chronisch nierenkranke Menschen - Schneider, Markus; Eckardt, Kai-Uwe (Deutsche Medizinische Wochenschrift, 2019)
Assessing the risk of adverse outcomes associated with chronic kidney disease (CKD) is important for physicians and affected patients alike. Categorizing CKD according to the cause-GFR category-albuminuria category (CGA)-classification system proposed by KDIGO already provides a semi-quantitative assessment of risks. The more recent development of the Tangri-formula provides a means to quantify the risk of progression for patients with CKD stage G3a-G5 (eGFR 10-59ml/min/1.73m 2) to kidney failure requiring kidney replacement therapy. To use this formula, the variables age, sex, eGFR and albuminuria are required (4-variable equation). An extended formula with the additional parameters calcium, phosphate, bicarbonate and albumin (8-variable equation) allows an even more precise estimation of progression risk. In patients with advanced CKD, stage G4 or higher (GFR category ≥4, i.e. eGFR <30ml/min/1.73m 2), models recently developed by the CKD-prognosis consortium can not only be used to predict the risk of kidney failure but also the risk of cardiovascular disease events and death. The risk estimators can be accessed through websites (http://kidneyfailurerisk.com, http://www.ckdpcrisk.org/lowgfrevents/) and via downloading of the respective apps. These novel tools may prove useful for health care decisions and as a basis for discussions with CKD patients.
CRIS-Team Scopus Importer:2019-06-18
Keywords: cardiovascular diseases; kidney; kidney disease; prognosis; risk

Risk Factors for Prognosis in Patients With Severely Decreased GFR - Evans, Marie; Grams, Morgan E.; Sang, Yingying; Astor, Brad C.; Blankestijn, Peter J.; Brunskill, Nigel J.; Collins, John F.; Kalra, Philip A.; Kovesdy, Csaba P.; Levin, Adeera; Mark, Patrick B.; Moranne, Olivier; et al. (Kidney International Reports, 2018)
Introduction: Patients with chronic kidney disease (CKD) and estimated glomerular filtration rate (eGFR) <30 ml/min per 1.73 m2 (corresponding to CKD stage G4+) comprise a minority of the overall CKD population but have the highest risk for adverse outcomes. Many CKD G4+ patients are older with multiple comorbidities, which may distort associations between risk factors and clinical outcomes. Methods: We undertook a meta-analysis of risk factors for kidney failure treated with kidney replacement therapy (KRT), cardiovascular disease (CVD) events, and death in participants with CKD G4+ from 28 cohorts (n = 185,024) across the world who were part of the CKD Prognosis Consortium. Results: In the fully adjusted meta-analysis, risk factors associated with KRT were time-varying CVD, male sex, black race, diabetes, lower eGFR, and higher albuminuria and systolic blood pressure. Age was associated with a lower risk of KRT (adjusted hazard ratio: 0.74; 95% confidence interval: 0.69-0.80) overall, and also in the subgroup of individuals younger than 65 years. The risk factors for CVD events included male sex, history of CVD, diabetes, lower eGFR, higher albuminuria, and the onset of KRT. Systolic blood pressure showed a U-shaped association with CVD events. Risk factors for mortality were similar to those for CVD events but also included smoking. Most risk factors had qualitatively consistent associations across cohorts. Conclusion: Traditional CVD risk factors are of prognostic value in individuals with an eGFR <30 ml/min per 1.73 m2, although the risk estimates vary for kidney and CVD outcomes. These results should encourage interventional studies on correcting risk factors in this high-risk population.
EVALuna2:215686

Serum levels of the Th1 chemoattractant interferon-gamma-inducible protein (IP) 10 are elevated in patients with essential hypertension - Stumpf, Christian; Auer, Claudia; Yilmaz, Atilla; Lewczuk, Piotr; Klinghammer, Lutz; Schneider, Markus; Daniel, Werner; Schmieder, Roland; Garlichs, Christoph (Hypertension Research, 2011)
Growing evidence shows that inflammation has a pivotal role in the pathophysiology of essential hypertension (EH). Although it has been acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages, but T lymphocytes have recently become the center of interest. The goal of our study was to evaluate the role of T-cell-specific cytokines in the pathogenesis of EH. The study examined 39 patients with EH (57.7±6.8 years, systolic blood pressure (SBP) 157.5±11.8 mm Hg, diastolic blood pressure 92.2±12.9 mm Hg, mean arterial pressure 113.9±12.6 mm Hg) and 30 healthy, normotensive controls (55.2±4.9 years). Blood was drawn from a peripheral vein, and serum levels of interferon-inducible protein (IP)-10 and interleukins (IL)-4,-7 and-13 were measured by a multiplexing assay. Hypertensive patients had significantly higher levels of IP-10, IL-4, IL-7 and IL-13 than control subjects. When the patients were classified into tertiles according to their serum IP-10 levels (T1: 41.2-9±4.1 pg ml-1; T2: 103.4-1±62.5 pg ml 1; T3: 171.7-443.5 pgml 1), the patients classified into the highest tertile also had the highest blood pressure. In a correlation analysis, plasma IP-10 concentration was significantly associated with SBP (r0.59, P<0.001). Furthermore, hypertensives with microalbuminuria, an early sign of hypertensive target organ damage, had the highest IP-10 levels. A stepwise multivariate regression analysis revealed IP-10 as the strongest independent predictor of SBP (P<0.01). In conclusion, our study provides new insights into the pathophysiological mechanisms in EH linking inflammation and IP-10. However, these preliminary results need to be confirmed in larger trials. © 2011 The Japanese Society of Hypertension All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: cytokines; inflammation; IP-10; microalbuminuria; T-cells

Spot urinary sodium in CKD patients: correlation with 24h-excretion and evaluation of commonly used prediction equations - Kurzhagen, Johanna; Titze, Stephanie; Büschges-Seraphin, Beatrix; Schiffer, Mario; Schneider, Markus; Eckardt, Kai-Uwe; Hilgers, Karl Friedrich (BMC Nephrology, 2024)
Background: Salt intake in CKD patients can affect cardiovascular risk and kidney disease progression. Twenty-four hour (24h) urine collections are often used to investigate salt metabolism but are cumbersome to perform. We assessed urinary sodium (U-Na) concentration in spot urine samples and investigated the correlation with 24h U-Na excretion and concentration in CKD patients under nephrological care. Further, we studied the role of CKD stage and diuretics and evaluated the performance of commonly used formulas for the prediction of 24h U-Na excretion from spot urine samples. Methods: One hundred eight patients of the German Chronic Kidney Disease (GCKD) study were included. Each participant collected a 24h urine and two spot urine samples within the same period. The first spot urine sample (AM) was part of the second morning urine. The second urine sample was collected before dinner (PM). Patients were advised to take their medication as usual without changing dietary habits. U-Na concentrations in the two spot urine samples and their average ((AM + PM)/2) were correlated with U-Na concentration and total Na excretion in the 24h urine collections. Correlations were subsequently studied after stratification by CKD stage and diuretic intake. The usefulness of three commonly applied equations to estimate 24h U-Na excretion from spot urine samples (Kawasaki, Tanaka and Intersalt) was determined using Bland–Altman plots, analyses of sensitivity, specificity, as well as positive (PPV) and negative predictive values (NPV). Results: Participants (42 women, 66 men) were on average (± SD) 62.2 (± 11.9) years old, with a mean serum creatinine of 1.6 (± 0.5) mg/dl. 95% had arterial hypertension, 37% diabetes mellitus and 55% were on diuretics. The best correlation with 24h U-Na total excretion was found for the PM spot U-Na sample. We also found strong correlations when comparing spot and 24h urine U-Na concentration. Correction of spot U-Na for U-creatinine did not improve strength of correlations. Neither CKD stage, nor intake of diuretics had significant impact on these correlations. All examined formulas revealed a significant mean bias. The lowest mean bias and the strongest correlation between estimated and measured U-Na excretion in 24h were obtained using the Tanaka-formula. Also, application of the Tanaka-formula with PM U-Na provided best sensitivity, specificity, PPV and NPV to estimate U-Na excretion > 4g/d corresponding to a salt consumption > 10g/d. Conclusion: U-Na concentration of spot urine samples correlated with 24h U-Na excretion especially when PM spot U-Na was used. However, correlation coefficients were relatively low. Neither CKD stage nor intake of diuretics appeared to have an influence on these correlations. There was a significant bias for all tested formulas with the Tanaka-formula providing the strongest correlation with measured 24h U-Na excretion. In summary, using spot urine samples together with the Tanaka-formula in epidemiological studies appears feasible to determine associations between approximate salt intake and outcomes in CKD patients. However, the usefulness of spot-urine samples to guide and monitor salt consumption in individual patients remains limited.
CRIS-Team Scopus Importer:2024-07-12
Keywords: 24h urine collection; Chronic kidney disease; Diuretics; Electrolytes; Salt; Sodium; Spot urine

Suboptimal monitoring and management in patients with unrecorded stage 3 chronic kidney disease in real-world settings: Insights from REVEAL-CKD - Tangri, Navdeep; Alvarez, Christian S.; Arnold, Matthew; Barone, Salvatore; Cebrián, Ana; Chen, Hungta; De Nicola, Luca; Järbrink, Krister; Kanumilli, Naresh; Lim, Kean Seng; Moriyama, Toshiki; Pecoits Filho, Roberto; et al. (European Journal of Clinical Investigation, 2024)
Background: Clinical practice guidelines for patients with chronic kidney disease (CKD) recommend regular monitoring and management of kidney function and CKD risk factors. However, the majority of patients with stage 3 CKD lack a diagnosis code, and data on the implementation of these recommendations in the real world are limited. Aim: To assess the implementation of guideline-directed monitoring and management practices in the real world in patients with stage 3 CKD without a recorded diagnosis code. Methods: REVEAL-CKD (NCT04847531) is a multinational, observational study of patients with stage 3 CKD. Eligible patients had ≥2 consecutive estimated glomerular filtration rate (eGFR) measurements indicative of stage 3 CKD recorded >90 and ≤730 days apart, lacked an International Classification of Diseases 9/10 diagnosis code corresponding to CKD any time before and up to 6 months after the second eGFR measurement. Testing of key measures of care quality were assessed. Results: The study included 435,971 patients from 9 countries. In all countries, the prevalence of urinary albumin–creatinine ratio and albuminuria testing was low. Angiotensin-converting enzyme inhibitor, angiotensin receptor blocker and statin prescriptions were highly variable, and sodium–glucose cotransporter-2 inhibitor prescriptions remained below 21%. Blood pressure measurements were recorded in 20.2%–89.9% of patients. Conclusions: Overall, a large proportion of patients with evidence of stage 3 CKD did not receive recommended, guideline-directed monitoring and management. The variability in standard of care among countries demonstrates a clear opportunity to improve monitoring and management of these patients, most likely improving long-term outcomes.
CRIS-Team Scopus Importer:2024-07-26
Keywords: chronic kidney disease; clinical guidelines; management; monitoring; real-world

The Cardiovascular Literature-Based Risk Algorithm (CALIBRA): Predicting Cardiovascular Events in Patients With Non-Dialysis Dependent Chronic Kidney Disease - Neri, Luca; Lonati, Caterina; Titapiccolo, Jasmine Ion; Nadal, Jennifer; Meiselbach, Heike; Schmid, Matthias; Baerthlein, Barbara; Tschulena, Ulrich; Schneider, Markus; Schultheiß, Ulla T.; Barbieri, Carlo; Moore, Christopher; et al. (Frontiers in Nephrology, 2022)
BACKGROUND AND OBJECTIVES: Cardiovascular (CV) disease is the main cause of morbidity and mortality in patients suffering from chronic kidney disease (CKD). Although it is widely recognized that CV risk assessment represents an essential prerequisite for clinical management, existing prognostic models appear not to be entirely adequate for CKD patients. We derived a literature-based, naïve-bayes model predicting the yearly risk of CV hospitalizations among patients suffering from CKD, referred as the CArdiovascular, LIterature-Based, Risk Algorithm (CALIBRA). METHODS: CALIBRA incorporates 31 variables including traditional and CKD-specific risk factors. It was validated in two independent CKD populations: the FMC NephroCare cohort (European Clinical Database, EuCliD®) and the German Chronic Kidney Disease (GCKD) study prospective cohort. CALIBRA performance was evaluated by c-statistics and calibration charts. In addition, CALIBRA discrimination was compared with that of three validated tools currently used for CV prediction in CKD, namely the Framingham Heart Study (FHS) risk score, the atherosclerotic cardiovascular disease risk score (ASCVD), and the Individual Data Analysis of Antihypertensive Intervention Trials (INDANA) calculator. Superiority was defined as a ΔAUC>0.05. RESULTS: CALIBRA showed good discrimination in both the EuCliD® medical registry (AUC 0.79, 95%CI 0.76-0.81) and the GCKD cohort (AUC 0.73, 95%CI 0.70-0.76). CALIBRA demonstrated improved accuracy compared to the benchmark models in EuCliD® (FHS: ΔAUC=-0.22, p<0.001; ASCVD: ΔAUC=-0.17, p<0.001; INDANA: ΔAUC=-0.14, p<0.001) and GCKD (FHS: ΔAUC=-0.16, p<0.001; ASCVD: ΔAUC=-0.12, p<0.001; INDANA: ΔAUC=-0.04, p<0.001) populations. Accuracy of the CALIBRA score was stable also for patients showing missing variables. CONCLUSION: CALIBRA provides accurate and robust stratification of CKD patients according to CV risk and allows score calculations with improved accuracy compared to established CV risk scores also in real-world clinical cohorts with considerable missingness rates. Our results support the generalizability of CALIBRA across different CKD populations and clinical settings.
EVALuna2:549060

Thyroid function, renal events and mortality in chronic kidney disease patients: the German Chronic Kidney Disease study - Schultheiss, Ulla T.; Steinbrenner, Inga; Nauck, Matthias; Schneider, Markus; Kotsis, Fruzsina; Baid-Agrawal, Seema; Schaeffner, Elke; Eckardt, Kai-Uwe; Koettgen, Anna; Sekula, Peggy (Clinical Kidney Journal, 2021)
Background. Hypothyroidism and low free triiodothyronine (FT3) syndrome [low FT3 levels with normal thyroid-stimulating hormone (TSH)] have been associated with reduced kidney function cross-sectionally in chronic kidney disease (CKD) patients with severely reduced estimated glomerular filtration rate (eGFR) or end-stage kidney disease (ESKD). Results on the prospective effects of impaired thyroid function on renal events and mortality for patients with severely reduced eGFR or from population-based cohorts are conflicting. Here we evaluated the association between thyroid and kidney function with eGFR (cross-sectionally) as well as renal events and mortality (prospectively) in a large, prospective cohort of CKD patients with mild to moderately reduced kidney function.
CRIS-Team WoS Importer:2021-05-28